COACHING (COACHING) PSYCHOLOGY AS AN IMPORTANT BRANCH OF APPLIED PSYCHOLOGY - Rustambekova Mamlakat Tillaevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article, the role of coaching psychology in Applied Psychology lies in the understanding of the identity of the individual, about the professional potential of the coach in the realization of goals and desires of envy, and, on this basis, about coaching technology and the fact that it serves as a powerful tool that contributes to the personal and communicative development of educators.